Baring it all: a study on the perceptions of school librarians and guidance counselors on pornography literacy - Estrellado, Dustin Matthew O.
Pornography has become popular to young people and present a danger to them because some may use it as a source of information. This could end up in misguided decisions that will cause sexual health problems in the future. Pornography literacy presents a promising solution that will increase young people’s awareness about pornography, its elements, its goals, and its representations.